UTILIZATION OF NIPAH FRUIT WASTE ACTIVATED CARBON AS ADSORBENT IN THE PURIFICATION PROCESS OF GLYCEROL BY-PRODUCTS OF PALM OIL BIODIESEL PRODUCTION - Kartikaningrum, Widhistya; Wijana , Susinggih; Pranowo, Dodyk (Jurnal Teknologi Industri Pertanian, 2024)
The glycerol residue from biodiesel production contains a lot of residue that makes it a low commercial value product with limited applications, so the glycerol residue is usually disposed of as waste in landfills. Therefore, this study aims to purify glycerol from palm biodiesel production by-products using an extraction-adsorption method. The first stage of the research was purification using petroleum ether and toluene extraction methods, followed by the adsorption stage using adsorbent in the form of activated carbon from nipah fruit waste which has an iodine adsorbing capacity of 966.978 ± 31.9433 mg/g and carbon surface area of 1066.3853 ± 35.2271 m2/g. Based on the results of FTIR testing, glycerol with adsorbent in the form of nipah fruit waste activated carbon characteristics are in accordance with commercial glycerol and the results of previous research, where the peak of O-H group is clearly formed at 3433.271 cm-1 and the peak of C-H group at 2934.672 cm-1. Based on the test results, the density value of the glycerol sample with nipah fruit waste activated carbon adsorbent was obtained with an average value of 1.255 ± 0.007 g/cm3 which was in accordance with British Standard (BS) 2621: 1979 of 1.2671 g/cm3. The test results obtained the value of the water content of the glycerol sample with nipah fruit waste activated carbon adsorbent with an average value of 8.563 ± 0.768% which is in accordance with British Standard (BS) 2621: 1979 of < 10%. The test results obtained the value of glycerol content of glycerol samples with activated carbon adsorbent of nipah fruit waste with an average value of 93.922 ± 2.523E0%. Keywords: adsorption, extraction, glycerol, activated carbon, nipah waste